2016
DOI: 10.17795/soj-3901
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of Primary Total Hip Arthroplasty via Lateral and Posterolateral Approaches

Abstract: Background: Total hip arthroplasty (THA) is regarded as the most successful and common surgical approach in orthopedic surgeries. Several surgical approaches have been described for THA to introduce minimally invasive surgical exposures. Posterolateral and lateral approaches are traditional and still most commonly used approaches for primary THA. In deciding which approach to use, consideration of complications, and clinical and radiological outcomes, using one approach or another should be evaluated. Objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(18 reference statements)
1
3
0
Order By: Relevance
“…These outcomes slightly lagged behind another study where the initial scores were lower but reached near-perfect scores at the six-month follow-up (20). Our study noted a dislocation rate of 4.1%, comparable to a previous study that observed a dislocation rate of approximately 3% in a larger cohort (21). Moreover, the limb length discrepancy significantly decreased post-operatively, aligning with literature suggesting that the lateral approach may confer a lower risk of dislocation (22,23).…”
Section: Discussionsupporting
confidence: 78%
“…These outcomes slightly lagged behind another study where the initial scores were lower but reached near-perfect scores at the six-month follow-up (20). Our study noted a dislocation rate of 4.1%, comparable to a previous study that observed a dislocation rate of approximately 3% in a larger cohort (21). Moreover, the limb length discrepancy significantly decreased post-operatively, aligning with literature suggesting that the lateral approach may confer a lower risk of dislocation (22,23).…”
Section: Discussionsupporting
confidence: 78%
“…Many of the previous studies reported similar perioperative bleeding volume between the two surgical approaches. [22][23]27,28] However, Weale et al showed a significantly lower mean perioperative blood loss in PA compared to LA (599 cc vs. 768 cc). [19] The overall perioperative bleeding volume following THA was found to be similar in both surgical approaches in a systematic review and meta-analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Most of the studies in the literature found post-operative blood transfusion to be similar among PA and LA. [21,23,27,29] However, Hart et al found that the proportion of patients requiring post-operative allogenic transfusion is significantly higher in LA than PA (11.55% vs. PA; 6.8%). [18] Our study revealed a relatively low complication rate following THA through PA than LA (7.0% vs. 12.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Gharanizade et al, which examined 134 patients who underwent primary hip arthroplasty, found that both the lateral and posterolateral approaches yielded similar results. Yet, disparities emerged regarding infections, DVT, proximal femur fractures, and limb length discrepancies (Gharanizade et al, 2016). The overarching conclusion was that both approaches facilitated effective pain reduction and restored function post-total hip arthroplasty.…”
Section: Discussionmentioning
confidence: 99%